Early-career faculty practice learner-centered teaching up to 9 years after postdoctoral professional development - Emery, Nathan C. (Sci Adv, 2020)
The goal of STEM professional development for teaching is that participants continue to practice what they learn in the long term. However, we do not know if the outcomes are achieved and ultimately persist. We tracked postdoctoral participants from the Faculty Institutes for Reforming Science Teaching (FIRST) IV program into their current positions as early-career biology faculty. We assessed their teaching approaches, practices, and student perceptions of the learning environment over 6 to 9 years after finishing the program. Simultaneously, we evaluated paired faculty in the same departments. We found that professional development outcomes persisted over time and across a career transition. FIRST IV faculty maintained their learner-centered practices and were more learner-centered than their peers. Last, we found that teaching approaches were correlated with teaching practices in all faculty participants. These results provide evidence for the success of the FIRST IV program and the long-term persistence of professional development outcomes.